PRACTICAL ASPECTS OF IMPLEMENTATION OF THE TERMS OF CRIMINAL PROCEDURE - Nerija Kovalenkovienė; Rasa Šemiotienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The criminal laws of the Republic of Lithuania defend and protect the most important values of human life. One of them is ensuring a proper and speedy criminal procedure, both when a person has been victimized by a criminal act, and also for persons who are being prosecuted. Although this individual right is guaranteed in the Criminal Procedure Code of the Republic of Lithuania (hereinafter referred to as the Code of Criminal Procedure of the Republic of Lithuania), the criminal procedure often lasts too long, violating the right of individuals to a speedy trial. What are the main problems that determine the delay of the investigation, how often is the delay of the procedure determined, and what are the possible consequences if the process is delayed for reasons other than objective ones – this is the main goal and relevance of this study. In this article, in order to determine the main reasons for the delay of both the pre-trial investigation and the judicial examination, an analysis of scientific literature and normative legal acts was carried out, as well as a qualitative study of the analysis of case law, which reveals the theoretical and practical issues of the implementation of criminal procedure deadlines. The scope of the study is the analysis of rulings of the Constitutional Court of the Republic of Lithuania, decisions of the European Court of Human Rights, and decisions of courts of general competence of the Republic of Lithuania in the period from 2014 to 2019 in criminal cases. The decisions made by the courts have been chosen, taking into account the most relevant insights, in order to reveal the problems of the implementation of the terms of the criminal procedure, as well as their observance without violating the rights and freedoms of individuals. In this article, in order to determine the main reasons for the delay of both the pre-trial investigation and the trial, the practice of both the national courts of general competence and the European Court of Human Rights was analysed. This research methodology aimed to analyse the main problem of this research - insufficient legal regulation, which would ensure the duty of law enforcement authorities to quickly and thoroughly reveal and investigate criminal acts, as well as to examine the case in court as soon as possible. The relevance of the issue lies in the possible consequences which arise when the duration of the criminal proceedings is recognized to be too long in Lithuania, in that case, the law provides for a lighter criminal liability for the defendant, which presupposes another possible legal problematic aspect: will the goals of the punishment be achieved if the sentence of the court of law is reduced due to the lengthy criminal procedure? Conclusions have been made regarding the impending consequences that may be caused by the length of the criminal procedure over a rather long period of time.